H.E.L.P India, Impossible as Possible - Lauth, Vincent (France, 2014)
According to the UN, the AIDS pandemic will be eradicated once India has overcome this plague. When and how ? This is a challenge that organizations as H.E.L.P India face in rural areas. In 10 years of research, the town of Andrah Pradesh has become an example of an original socio-medical system with the same results than western countries. Manjula, Mariya, Prameela and all the women from the HKKK workshop are the ambassadors of this success,not only because they stabilized their health and found their joy of living again, but also because they became talented Kalamkari professional artists, a traditional way of painting.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films